2007
DOI: 10.1590/s1415-52732007000200003
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade microbiológica e temperatura de dietas enterais antes e após implantação do sistema de análise de perigos e pontos críticos de controle

Abstract: OBJETIVOS: Avaliar a qualidade microbiológica e a temperatura de dietas enterais antes e após a implementação do sistema Análise de Perigos e Pontos Críticos de Controle na Central de Produção de Alimentação Enteral do Hospital de Clínicas de Porto Alegre. MÉTODOS: Durante o período de setembro de 2001 a janeiro de 2002, foram coletadas 320 amostras de 4 tipos de dietas enterais produzidas na Central de Produção de Alimentação Enteral (dietas padrão I, II, III e dieta especial), as quais foram submetidas a aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
2
4
2
1
Order By: Relevance
“…These results agree with those obtained by Sousa and Campos (2003), Lima et al. (2005) and Simon et al. (2007), who found that all enteral diet samples analyzed were negative for S. aureus .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These results agree with those obtained by Sousa and Campos (2003), Lima et al. (2005) and Simon et al. (2007), who found that all enteral diet samples analyzed were negative for S. aureus .…”
Section: Resultssupporting
confidence: 92%
“…The percentage of diet samples contaminated above the limits established by legislation in H1 and H2 (25.0 and 27.5%, respectively) were higher than those presented by Lima et al. (2005), who found 20.0% of samples contaminated, ranging from 1.1 × 10 3 to 7.4 × 10 4 cfu/mL, and higher than the results presented by Simon et al. (2007), who found 16.2% of samples in violation of legislation.…”
Section: Resultscontrasting
confidence: 62%
See 3 more Smart Citations